The experiences of autistic doctors: a cross-sectional study - Shaw, Sebastian C. K.; Fossi, Alexander; Carravallah, Laura A.; Rabenstein, Kai; Ross, Wendy; Doherty, Mary (Frontiers in Psychiatry, 2023)
Introduction: Medicine may select for autistic characteristics. As awareness and diagnosis of autism are growing, more medical students and doctors may be discovering they are autistic. No studies have explored the experiences of autistic doctors. This study aimed to fill that gap. Methods: This is a cross-sectional study. A participatory approach was used to identify the need for the project and to modify a pre-existing survey for use exploring the experiences of autistic doctors. Results: We received 225 responses. 64% had a formal diagnosis of autism. The mean age of receiving a formal diagnosis was 36 (range 3-61). Most were currently working as doctors (82%). The most common specialties were general practice / family medicine (31%), psychiatry (18%), and anaesthesia (11%). Almost half of those working had completed specialty training (46%) and 40% were current trainees. 29% had not disclosed being autistic to anyone at work. 46% had requested adjustments in the workplace but of these, only half had them implemented. Three quarters had considered suicide (77%), one quarter had attempted suicide (24%) and half had engaged in self-harm (49%). 80% reported having worked with another doctor they suspected was autistic, but only 22% reported having worked with another doctor they knew was autistic. Having never worked with a potentially autistic colleague was associated with having considered suicide. Most preferred to be called “autistic doctors” (64%). Most considered autism to be a difference (83%). Considering autism to be a disorder was associated with preference for the term “doctors with autism”, and with having attempted suicide. Conclusions: Autistic doctors reported many challenges in the workplace. This may have contributed to a culture of nondisclosure. Mental health was poor with high rates of suicidal ideation, self-harm, and prior suicide attempts. Despite inhospitable environments, most were persevering and working successfully. Viewing autism as a disorder was associated with prior suicide attempts and a preference for person-first language. A neurodiversity-affirmative approach to autism may lead to a more positive self-identity and improved mental health. Furthermore, providing adequate supports and improving awareness of autistic medical professionals may promote inclusion in the medical workforce.